ISLAMIC STUDENT ORGANIZATIONS' STRATEGY OF COMMUNICATING AND MAINTAINING ISLAMIST IDEOLOGY AMONG UNIVERSITY STUDENTS IN EAST KALIMANTAN - Mukhamad Ilyasin; Miftahur Ridho (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
This paper aims to explain the role of KAMMI (Kesatuan Aksi Mahasiswa Muslim Indonesia/ the Indonesian Muslim University Students Action Union) in Universities in East Kalimantan in shaping the political dynamics among students in university settings. Utilizing a qualitative approach to analyze data collected through interviews with members of KAMMI in Samarinda, findings reveal that KAMMI’s main strategy to maintain its’ Islamist ideology consists of three distinctive steps: 1) introducing KAMMI to potential members in high schools via vacation trip program (rihlah); 2) recruiting members during admission time via personal approaches; and 3) maintaining solidarity by utilizing small circle study groups. In the first two steps, KAMMI would introduce potential new members with personal holiness, which aims to guard the students' morality. In the third phase, members would be familiarized with the concept of “Muslim Negarawan,” in which they are asked to view their campus as a political arena of competition for power.